2020
DOI: 10.5864/d2020-009
|View full text |Cite
|
Sign up to set email alerts
|

Death care during the COVID-19 pandemic: understanding the public health risks

Abstract: A global pandemic can place extraordinary strain on health care resources, and where widespread fatalities occur, this can have concomitant effects for the death care sector. Uncertainties can arise, particularly for a novel pathogen, on likely routes of transmission, viability of the pathogen in different settings, and appropriate measures required to minimize risks to those working in the death care sector or family members and others who come into contact with the deceased. This paper provides an overview o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Many offices had to change their procedures when handling decedents, assuming that all of them could carry the virus. While death investigators already wear personal protective equipment and take precautions when handling bodies, more care was needed to ensure personnel did not contract the virus during each stage of the death management process (O'Keefe, 2020).…”
Section: Covid‐19 As a Mass Fatality Eventmentioning
confidence: 99%
“…Many offices had to change their procedures when handling decedents, assuming that all of them could carry the virus. While death investigators already wear personal protective equipment and take precautions when handling bodies, more care was needed to ensure personnel did not contract the virus during each stage of the death management process (O'Keefe, 2020).…”
Section: Covid‐19 As a Mass Fatality Eventmentioning
confidence: 99%
“…It is well known among respiratory disease researchers, for instance, that bodies transmit viruses through the usual emissions like coughing and sneezing, but also through singing, laughing and speaking (Stelzer-Braid et al, 2009). A review by the National Collaborating Centre for Environmental Health (O’Keeffe, 2020) has revealed that choir rehearsals may still be considered superspreader events, despite participants avoiding handshakes and maintaining the recommended social distance. Singing, laughing and talking are thus included, along with physical touch, among activities that we must take stock of in our interactions, though these actions are deeply embedded in our sense of value in the very basic structures of communication.…”
Section: The World Of the Virus Or The Virus Of The World?mentioning
confidence: 99%
“…Early in the pandemic, music ensembles made headlines following several "superspreader events" that took place at choir rehearsals [1,2]. The risk undertaken by singers was scrutinized most closely, given their reliance on breath for sound production and their habit of performing in close proximity to one another using resonant indoor spaces [3,4]. Emphasis was placed on the dispersal of aerosols and droplets, which also accompanies sound production in wind instruments [5,6].…”
Section: Introductionmentioning
confidence: 99%